Soil-Transmitted Helminths Infections among Fewer than 5 Children and Associated Environmental Factors in Selected Maternal Healthcare Centres in Ibadan, Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Soil transmitted helminth infections are among the most common human infections. They are distributed throughout the world with high prevalence rates in tropical and sub-tropical countries mainly because of lack of adequate sanitary facilities, inappropriate waste disposal systems, lack of safe water supply, and low socio-economic status. Therefore, this study was designed to investigate the prevalence of Soil transmitted helminth infections in stool samples obtained from selected under five children in maternal healthcare centers in Ibadan. The objectives of this study were to determine the prevalence, associated environmental factors of STH infections and identify the types of STH present. A cross sectional survey was conducted among 384 people in two maternal healthcare centers in Ibadan. A total of 100 stool samples were collected from two different locations and parasitological examination of the stool samples were done for the presence of STH eggs using a Kato-Katz thick smear technique. In addition, questionnaires were given out to each respondent asking about their awareness of the etiology, symptoms, risk factors for infection, level of cleanliness, and sanitation. The geographic distribution of STH prevalence was identified. About 69% of the respondents' age group falls between 25-34years. The average age of respondents is 31.41±5.33. The parasitological examination of the 100 stool samples collected showed that 36% were positive for STHs. Parasite types found included Hookworm (Necator americanus (20.9%) and Ancylostoma duodenale (20.6%)), Trichuris trichiura (24.8%) and Ascaris lumbricoides (37.5%). Adeoyo hospital had the highest prevalence of Ascaris (26.1%) while Oni and Sons hospital had the highest prevalence of Trichuris (24.8%). The male gender had a higher infection of Ascaris (52.4%) while the female gender had a higher infection rate of Trichuris (72.7%). There was no statistical relationship between knowledge of STH and infections. The presence of viable STHs eggs/ larvae in soil suggests possible active transmission and high rate of exposure to infective agents among the school children. Higher prevalence of soil transmitted helminth infection was found among government school students. Thus, more focus, on personal hygiene and sanitary facilities, should be given to children.